Multiple violations of labor market regulations: Patterns in the Peruvian labor market and the impact of enforcement - Mariana Viollaz (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2019)
This paper quantifies labor law violations and how the enforcement efforts impact on the compliance level by considering the possibility of different labor regulations being violated simultaneously. The findings for the Peruvian labor markets over the period 2004-2013 indicate that: (i) multiple violations of labor regulations are an important feature of Peruvian labor markets; (ii) young workers, workers with low level of education, indigenous workers, workers in micro firms and workers employed in the agricultural sector have higher chances of being deprived of several labor benefits simultaneously; (iii) the enforcement of labor regulations, captured through the number of labor inspections at the region level, is effective in detecting and penalizing extreme situations of multiple violations of the labor law, but the evidence also suggests that firms adjust only partially as an attempt to reduce the amount of a potential fine if discovered, and that laid off workers during the adjustment process moved to the informal sector where firms are not inspected. These findings are useful from a policy perspective indicating that there is space to improve firms' incentives when facing an increase in the enforcement effort.
Keywords: I20; J24; J45; J52; J16; 330; Multiple violations; Labor market regulations; Enforcement; Peru